Management of the residual pleural space after lung resection: phrenic nerve block, pneumoperitoneum and chemical pleurodesis: 2 clinical cases - Sastre, Ignacio; España, Manuel; Ceballos, Roberto; Siri, Juan; Bustos, Mario E.F (Cirugía del Uruguay, 2020)
The residual pleural space after lung resection associated with air leak is a frequent finding. It is reported that it can occur in up to 40% of patients in the first postoperative days. Treatment may require re-surgery or the use of less invasive procedures. In two patients, we performed cervical phrenic nerve block, pneumoperitoneum, and chemical pleurodesis by drainage tube.